Isoimperatorin, a natural furanocoumarin, ameliorates ulcerative colitis by inducing Treg cell generation and promoting mucosal healing - Yulai Fang; Shichen Min; Hongxin Chen; Zhenxing Zhu; Yanan Li; Yiheng Tong; Jingyi Hu; Lei Zhu; Hong Shen (Molecular Medicine)
Abstract Background Ulcerative colitis (UC), an autoimmune disorder characterized by chronic intestinal inflammation, primarily targets the colonic mucosa. Isoimperatorin is a natural furanocoumarin compound with a variety of pharmacological activities. However, its therapeutic potential and underlying mechanisms in UC pathogenesis remain to be elucidated. Methods Mice were administered 2.5% dextran sulfate sodium (DSS) ad libitum to construct a colitis model, and isoimperatorin was given by gavage to evaluate its efficacy. Flow cytometry and qPCR were employed to assess the effect of isoimperatorin on Treg cell generation. Tissue immunofluorescence and Western blot were used to investigate the effects of isoimperatorin on the repair of damaged intestinal barrier. Cell scratching and migration were used to examine the effects of isoimperatorin on wound healing and cell migration. Finally, a Treg cell depletion assay was implemented to verify the Treg cell-dependent effect of isoimperatorin on repairing intestinal barrier injury to ameliorate UC. Results Oral gavage administration of isoimperatorin (20, 40 mg/kg) significantly improved disease symptoms in UC mice. Isoimperatorin treatment elevated the percentage of Treg cells but had no significant effect on the proportion of Th17 cells in mesenteric lymph node tissues. Isoimperatorin upregulated the expression levels of factors related to mucosal healing and upregulated the expression levels of proteins related to the integrity of the intestinal epithelial barrier. Additionally, isoimperatorin (1, 3 µM) accelerated the migration of colon epithelial cells to facilitate wound healing and also induced the generation of Treg cells in vitro. Finally, Treg cell depletion markedly attenuated isoimperatorin’s therapeutic efficacy in intestinal barrier repair and UC amelioration, indicating a Treg cell-dependent mechanism of action. Conclusions Isoimperatorin promotes intestinal mucosal healing and thus improves UC disease symptoms by inducing Treg cell generation.